Implementasi Metode Extract, Transform, Load (ETL) untuk Visualisasi Data Penjualan Café Menggunakan Google Looker Studio - Amanda, Aliza Fatha; Waspodo, Bayu (LPPM Universitas Dinamika Bangsa, 2025)
Café Durian Woke is a culinary business that focuses on selling various foods and beverages made from durian. The problem faced is that sales reports on the Olsera cashier system are still presented in tabular form, making it difficult for management to understand sales trends and make strategic evaluations and decisions. This study aims to develop sales data visualization for Café Durian Woke using Google Looker Studio tools with an Extract, Transform, Load (ETL) approach. The ETL method is used to extract transaction data, clean and transform the data using Microsoft Excel, and then load the results into Looker Studio for interactive visualization. The results of the study show that the developed dashboard is capable of displaying important information such as product sales trends, customer categories, and purchasing methods, where dine-in transactions dominate 93.3% of total sales. This visualization helps management identify superior products, understand customer behavior, and support faster, data-driven decision making.